An Analysis on The Effect of Computer Literacy and Attitude Towards Internet Amongst Generation Y - Pathmananathan, P. Ravindran; Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2021)
The Internet continues to change and evolve against a backdrop of unrelenting growth The Internet developed a ground-breaking open model for its own growth and governance that included all stakeholders.Generation Y has been recognized as a new market segment that will bring change in the platform of internet in an enormously connected world. The aim of this study is to analyze the attitude and the Internet usage among the generation. This study was carried out via a questionnaire involving 432 working professional who live around Kuala Lumpur Federal Territory and Selangor State, more precisely the author has selected MSC (Multimedia Super Corridor). It can be concluded that their attitude toward the internet played a significant role in their e-commerce activities and was a predicted factor. It is apparent that attitudes toward the internet and e-commerce practises have a major relationship.